Spatially varying relationships between immigration measures and property crime Types in Vancouver Census Tracts, 2016 - Andresen, Martin A. (The British journal of criminology, 2020)
We empirically test for spatial heterogeneity or local effects of multiple immigration measures on various property crime classification across Vancouver census tracts, 2016. Using spatially referenced property crime data and census data, we use geographically weighted regression to investigate the neighbourhood-level effects of immigration on crime. We find that estimated parameters vary across space, but these local immigration effects do not always vary significantly at the local level. Overall, significant spatial variation in the effects of immigration on property crime is present. These are important for policy and theory. The identification of varied spatial patterns of immigration effects on crime may help explain some of the inconsistent/disparate results found in neighbourhood-level studies on immigration and crime.